2002
DOI: 10.1063/1.1499232
|View full text |Cite
|
Sign up to set email alerts
|

Crystal size and oxygen segregation for polycrystalline GaN

Abstract: The grain size for polycrystalline GaN, grown in low-temperature gallium-rich conditions, is shown to be correlated to the oxygen content of the films. Films with lower oxygen content were observed to have larger crystals with an increased tendency to a single-preferred crystal orientation. Elastic recoil detection analysis with heavy ions (i.e., 200 MeV Au 197 ions) was used to determine the composition of the GaN films grown for the study, including the hydrogen, carbon, gallium, nitrogen, and oxygen content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…The bonding configuration of such high concentrations of a chalcogenide in disordered GaN is unlikely to be exclusively tetrahedral, as evidenced by observations that in high concentrations oxygen impurities in c-GaN reside in dislocations and grain boundaries rather than as a simple nitrogen substituent [26,27]. We suggest that it forms either two-or four-fold bonds, primarily with Ga ions, which reduces the density of exclusively tetrahedral bonds and permits a space-filling network even within the even-membered ring constraint.…”
mentioning
confidence: 99%
“…The bonding configuration of such high concentrations of a chalcogenide in disordered GaN is unlikely to be exclusively tetrahedral, as evidenced by observations that in high concentrations oxygen impurities in c-GaN reside in dislocations and grain boundaries rather than as a simple nitrogen substituent [26,27]. We suggest that it forms either two-or four-fold bonds, primarily with Ga ions, which reduces the density of exclusively tetrahedral bonds and permits a space-filling network even within the even-membered ring constraint.…”
mentioning
confidence: 99%
“…In other words, interactions between point defects and dislocations are inevitable and even energetically favored [16]. On the experimental side, it has been shown that dislocations in GaN cause O segregation [8,[17][18][19], as well as enhancing O diffusion [20,21]. Recently, O annealing was found to increase the electrical performance of AlGaN/GaN, which has been attributed to an O passivation effect of the dislocations [22].…”
mentioning
confidence: 99%
“…While single crystal films are available for both materials, polycrystalline films of GaN and InN may offer alternatives for many applications. Polycrystalline GaN films can be produced at considerably lower deposition temperatures (<650°C) than material of single crystal quality [4]. Also, substrates other than sapphire or SiC can be used.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort towards such an understanding, a correlation has been established between oxygen incorporation and grain-size for polycrystalline GaN films deposited with remote plasma enhanced laser induced chemical vapour deposition [4]. The stoichiometric information was obtained with elastic recoil detection (ERD) using an incident beam of 200 MeV 197 Au ions [7].…”
Section: Introductionmentioning
confidence: 99%